2022
DOI: 10.1172/jci.insight.153359
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitor of intestinal anion exchanger SLC26A3 for treatment of hyperoxaluria and nephrolithiasis

Abstract: Nephrolithiasis is a common and recurrent disease affecting 9% of the US population. Hyperoxaluria is major risk factor for calcium oxalate kidney stones, which constitute two-thirds of all kidney stones. SLC26A3 (DRA, downregulated in adenoma) is an anion exchanger of chloride, bicarbonate, and oxalate thought to facilitate intestinal oxalate absorption, as evidenced by approximately 70% reduced urine oxalate excretion in knockout mice. We previously identified a small-molecule SLC26A3 inhibitor (DRA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Over the past decade, researchers have suggested that SLC26A3 may serve as a therapeutic target to treat hyperoxaluria and prevent CaOx urolithiasis. CIL et al (2022) demonstrated that DRAinh-A270 selectively inhibits SLC26A3-mediated chloride/bicarbonate exchange. Notably, the same study reported that the reduced function of SLC26A3 mutants, which may decrease male fertility, may be caused by a weakened interaction between the specific structural domain STAS and the cystic fibrosis transmembrane conductance-regulated channel, thereby affecting chloride transport.…”
Section: Slc26 Proteins In the Kidneymentioning
confidence: 97%
“…Over the past decade, researchers have suggested that SLC26A3 may serve as a therapeutic target to treat hyperoxaluria and prevent CaOx urolithiasis. CIL et al (2022) demonstrated that DRAinh-A270 selectively inhibits SLC26A3-mediated chloride/bicarbonate exchange. Notably, the same study reported that the reduced function of SLC26A3 mutants, which may decrease male fertility, may be caused by a weakened interaction between the specific structural domain STAS and the cystic fibrosis transmembrane conductance-regulated channel, thereby affecting chloride transport.…”
Section: Slc26 Proteins In the Kidneymentioning
confidence: 97%
“…Ions, amino acids and their transporters and channels, calcium-sensitive receptor signaling pathways, and the metabolic pathways of vitamin D, oxalic acid, cysteine, purine and uric acid are considered to play key roles in the etiology of kidney stones ( 42 ). CaOx stones formed due to hyperoxaluria account for approximately two-thirds of all kidney stones ( 43 ). In HK-2 cells, oxalate activates ERS/ROS via NF-κB-dependent pathways, causing autophagy, apoptosis and mitochondrial damage ( 44 ).…”
Section: The Various Forms Of Cell Death and Urolithiasismentioning
confidence: 99%
“…4,5 To prevent stone recurrence, lifestyle changes and preventive medical treatment are used. 6 Hyperoxaluria is a major risk factor for calcium oxalate stones, 7 the most common type constituting 2/3 of all kidney stones. 8 Currently, medical treatment options for kidney stones are limited and there are no approved treatments for hyperoxaluria.…”
Section: Introductionmentioning
confidence: 99%